Efektivitas Model Pictorial Riddle Berbantuan Aplikasi Qreatif terhadap Pemahaman Konsep Dan Aktivitas Belajar Siswa Kelas III SDN Wonosari 01 - Somo, Somo; Kiptiyah, Siti Maryatul (FONDATIA, 2024)
Problems in learning IPAS in primary schools often arise, especially in the use of monotonous teaching methods and media that do not support active participation of students so that they can cause misconceptions in students. These problems need to be overcome by using the right learning model and media. This study aims to examine the effectiveness of Pictorial Riddle learning model with Qreatif application on students' concept understanding and learning activities. The type of research used is quantitative with a Quasi Experimental design of the Non-equivalent Control Group Design type. The study population was 51 third grade students of SDN Wonosari 01. The sample was obtained through saturated sampling technique. The experimental class used Pictorial Riddle model and Qreatif media, while the control class used conventional model and Canva PPT. Data were collected through test and non-test techniques. Data analysis techniques included normality test, homogeneity test, hypothesis test (t-test), and N-gain test. The t-test results showed a significant difference in concept understanding between the experimental and control classes with a 2-tailed sig value of less than 0.05 (0.001 < 0.05) and a t-count value of 7.340 > t-table 2.009. The number of students who completed the KKM in the experimental class was greater than the control class (88%> 46%) this indicates a difference in understanding the concepts of the control and experimental classes. The mean N-Gain value of the experimental class is higher than the control class (65.60% > 42.05%). Analysis of student activeness scores showed that the experimental class was higher than the control class (observation: 84% > 66%; questionnaire: 81% > 66%). In conclusion, the Pictorial Riddle learning model with Qreatif application is effective in improving students' concept understanding and learning activities.